Perbandingan Tulangan Kolom dan Deformasi Struktur Gedung - Alamsyah, Syahrul; Setiawan, Wira; Apriansyah, Muh; Zulfikar, M. Deta; Syaputri, Sulis; Fikar, M. Ziaul (Local Engineering, 2026)
The Moment-Resisting Frame System (MRFS) equipped with shear walls shows a significant increase in structural stiffness compared to systems without shear walls. The results of the inter-storey drift analysis confirm that the presence of shear walls reduces the horizontal deformation of the building, thereby increasing lateral stability. In addition, the use of shear walls contributes to the efficiency of reinforcement requirements, as seen in the column reinforcement ratio of 3%, which is lower than that of structures without shear walls, which reaches 5%. Although the mass of the structure with shear walls is greater, namely 4747.96 kN compared to 3853.08 kN in structures without shear walls, this system still offers advantages in terms of more efficient use of main reinforcement. Overall, the integration of shear walls in the frame system provides better structural performance through increased stiffness, reduced deflection, and optimised reinforcement requirements.